Superior photothermal conversion performance of black titanium-based materials - Jun Li; Enhui Wu; Zhong Xu; Jing Hou; Wenjing Peng; Hong Li; Xiang Li (iScience)
Summary: The application of photothermal conversion technology in the fields of seawater desalination and wastewater treatment stands as a potent approach to alleviating the global water scarcity crisis. In this research, we have successfully synthesized black titanium-based photothermal conversion materials utilizing the aluminothermic reduction method. The experimental results demonstrate that the crafted black TiO2 exhibits a notable overall solar energy absorptivity of 65.7% and a photothermal conversion efficiency of 87.5%. Notably, the black Magneli phase titanium oxide (Ti4O7 and Ti5O9), derived from nanorutile TiO2, exhibits an even more impressive overall solar absorptivity of 83.4% and a photothermal conversion efficiency of 93.8%. Under a light intensity of 5 kW/m2, this material achieves an evaporation rate of 4.4 kg m−2·h−1 and an evaporation efficiency of 63%, underscoring its vast potential for applications in wastewater purification and seawater desalination.